1993
DOI: 10.1128/jvi.67.2.961-968.1993
|View full text |Cite
|
Sign up to set email alerts
|

An antibody- and synthetic peptide-defined rubella virus E1 glycoprotein neutralization domain

Abstract: We previously described a monoclonal antibody (MAb) library generated by infecting BALB/c mice with rubella virus (RV) and selected by an enzyme-linked immunosorbent assay (ELISA) using purified virion targets. Plasmid pARV02-01, which expresses the fusion protein RecA1_35-GIGDLGSP-E1202-E1283-GDP-LacZ>1015 in Escherichia coli, was shown to be a ligand for MAbs E1-18 and E1-20 (J. S. Wolinsky, M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 49 publications
(60 reference statements)
0
21
0
Order By: Relevance
“…The functions of the RV E1 and E2 glycoproteins have been studied extensively. Using monoclonal antibodies, it has been shown that the E1 protein contains at least six nonoverlapping epitopes, some of which are associated with hemagglutination and neutralization (21,67,139,140,152,160,161). E1 appears to be the main surface protein, with domains involved in the attachment of the virus to the cell.…”
Section: E1 and E2 Glycoproteinsmentioning
confidence: 99%
“…The functions of the RV E1 and E2 glycoproteins have been studied extensively. Using monoclonal antibodies, it has been shown that the E1 protein contains at least six nonoverlapping epitopes, some of which are associated with hemagglutination and neutralization (21,67,139,140,152,160,161). E1 appears to be the main surface protein, with domains involved in the attachment of the virus to the cell.…”
Section: E1 and E2 Glycoproteinsmentioning
confidence: 99%
“…RV contains three major antigens: the envelope glycoproteins (El and E2) and an internal capsid protein [11,12]. Four nonoverlapping domains that are binding sites for RV-neutralizing antibodies have been located within residues 213-285 on E1 [12,[14][15][16][17][18]. At least four T-cell antigenic sites within this sequence have also been mapped by using peripheral blood mononuclear cells (PBMNCs) or CD4 + T-cell lines in lymphoproliferation screening assays employing relatively long (16-33 aa) SPs [14,[19][20][21].…”
Section: Analysis Of Overlapping T-and B-cell Antigenic Sites On Rubementioning
confidence: 99%
“…a P values for comparisons between subjects whose sera exhibited a shift in immunoblot pattern from those subjects whose postvaccination sera exhibited no change in RV protein specificities as determined by IgG immunoblot assays. 239 (29,46), which is one of four known NT domains on this protein (8,40,43). GMTs and median antibody levels measured by the three whole-RV EIAs were determined to be well above their established negative cutoff points, suggesting that the majority of the individuals studied had protective levels of RV-specific IgG both before and after receiving the MMR vaccine.…”
Section: Discussionmentioning
confidence: 87%
“…RV has three major antigenic proteins: the envelope glycoproteins E1 and E2 and the internal capsid protein C. The protein most characterized biologically is E1, which contains four NT domains as well as the target sequence for HAI antibodies (8,40,43) located between amino acid residues 209 and 291. Synthetic peptides have been used to map one NT domain located between E1 residues 213 and 239 recognized by both murine and human antibodies (29).…”
mentioning
confidence: 99%